THE QUALITY OF LIFE OF PATIENTS WITH CIRRHOSIS OF THE LIVER DEPENDING ON THE TONE OF THE AUTONOMIC NERVOUS SYSTEM - Yarmatov Suvon Totlibayevich (European Journal of Humanities and Educational Advancements, 2022)
Currently, much attention is paid in medicine to the study of the quality of life (QOL) of patients. Being investigated the relationship between QOL and the course of the disease, the characteristics of the patient’s personality. The presented study involved 139 patients with cirrhosis of the liver (CP). With the help of questionnaires independently filled out by patients, QOL was assessed depending on the tone of the autonomic nervous system. As a result of observation, it was found that vegetative imbalance in patients with cirrhosis of the liver with a predominance of parasympathetic influences worsens QOL indicators in the areas of energy, pain and emotional reactions.